The impact of family function on post-traumatic reactions of Chinese adolescents infected with COVID-19: a latent profile study - Xu, Mingtu; Tian, Runhui; Fu, Cong; Li, Jingyang; Bi, Dingyu; Wang, Yan (Frontiers in Public Health, 2023)
Background Since the end of 2019, Corona Virus Disease 2019, also known as COVID-19, has broken out in various countries. However, the change of China's COVID-19 prevention and control policy and the sharp increase in the number of infected people are making the teenagers have post-traumatic reactions. Negative post-traumatic reactions include: post-traumatic stress disorder (PTSD), depression, anxiety. Positive post-traumatic reaction mainly refers to post-traumatic growth (PTG). The purpose of this study is to explore the post-traumatic reaction, which refers to PTSD, depression, anxiety and the co-occurrence pattern of growth after trauma and to further explore the influence of family function on different categories of Post-traumatic Reactions. Methods Latent profile analysis (LPA) was used to explore the co-occurrence of PTSD, depression, anxiety, and PTG. Multiple logistics regression was used to analyze the influence of family function on different categories of post-traumatic response. Results There were three categories of post-traumatic reactions in adolescents infected with COVID-19 adolescents infected with COVID-19, namely: growth class, struggling class, and pain class. Multivariate Logistic regression showed that the growth class and struggling class were affected by problem solving and behavior control in family function, while the growth class and pain class were affected by problem solving, roles, behavior control, and general functioning. Multiple logistic regression showed that the growth class and struggling class were affected by problem solving and roles. Conclusions The findings of this study provide evidence for the identification of high-risk individuals and the provision of effective interventions in clinical practice, as well as the influence of family functioning on the different categories of PTSD among adolescents infected with COVID-19.